2010
DOI: 10.2131/jts.35.197
|View full text |Cite
|
Sign up to set email alerts
|

Toluene diisocyanate (TDI) induces calcium elevation and interleukine-4 (IL-4) release - Early responses upon TDI stimulation

Abstract: -Occupational exposure to toluene diisocyanats (TDI) may cause asthma. In asthma patients, the allergic syndromes correlate cytokine production with the elevation in cytosolic calcium concentration [Ca 2+ ] c of lymphocytes in airway. We previously found TDI induces calcium signaling in neuronal cells. TDI mainly gets into human body via inhalation; therefore this study investigated the possibility of TDI inducing the changes in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Another finding, which was made more evident by GeneMANIA, was that calcium regulation networks were associated with both HDA and TAHI via the regulation of bone mineralization by the BMP receptors ACVR1 and BMPR1B, respectively. These results are supportive of findings by Chiung and colleagues, in which they demonstrated that in vitro exposure to a related isocyanate, TDI, resulted in elevated calcium levels in the cells (Chiung et al, 2010). They also showed that the increase in calcium triggered the release of the pro-inflammatory cytokine interleukin-4 (IL4) (Chiung et al, 2010).…”
Section: Bioinformaticssupporting
confidence: 88%
See 1 more Smart Citation
“…Another finding, which was made more evident by GeneMANIA, was that calcium regulation networks were associated with both HDA and TAHI via the regulation of bone mineralization by the BMP receptors ACVR1 and BMPR1B, respectively. These results are supportive of findings by Chiung and colleagues, in which they demonstrated that in vitro exposure to a related isocyanate, TDI, resulted in elevated calcium levels in the cells (Chiung et al, 2010). They also showed that the increase in calcium triggered the release of the pro-inflammatory cytokine interleukin-4 (IL4) (Chiung et al, 2010).…”
Section: Bioinformaticssupporting
confidence: 88%
“…These results are supportive of findings by Chiung and colleagues, in which they demonstrated that in vitro exposure to a related isocyanate, TDI, resulted in elevated calcium levels in the cells (Chiung et al, 2010). They also showed that the increase in calcium triggered the release of the pro-inflammatory cytokine interleukin-4 (IL4) (Chiung et al, 2010). Additionally, research on isocyanate-induced asthma has correlated a calciumdependent cell adhesion gene, CDH17, with isocyanate asthma risk (Yucesoy et al, 2015a;Bernstein et al, 2018).…”
Section: Bioinformaticssupporting
confidence: 84%
“…Elevated levels of both T-helper (T H )-1 and T H 2 cytokines have been demonstrated in the airways of subjects with different asthma phenotypes, supporting the heterogenic nature of disease (Broide et al, 1992; Fisseler-Eckhoff et al, 2011; Maestrelli et al, 1995, 1997; Mapp et al, 2009; Piirila et al, 2008). Animal and in vitro models revealed multiple roles of cytokines in non-specific inflammatory processes as well as specific immune events in response to diisocyanate exposure (Chiung et al, 2010; Matheson et al, 2002; Swierczynska-Machura et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure to toluene diisocyante (TDI) can occur during production, handling and use, 94 and emissions from urethane production facilities can lead to exposure in the general population. 95 TDI-induced asthma shares similarities with common environmental asthma (natural history, clinical symptoms, and pathology) but also differences (minimal Th2 response, minimal association of atopy, allergen-specific IgE and serum levels of total IgE). 96 In this model, mice were dermally sensitized to TDI on days 1 and 8 and oropharyngeally challenged with NPs on day 14.…”
Section: Box 3 Animal Models For Asthmamentioning
confidence: 98%
“…They are used in the production of polyurethane, which has diverse industrial applications (production of foams, durable elastomeric wheels and tires, automotive suspension bushings, electrical potting compounds, high performance adhesives and sealants, seals, gaskets, carpets). Occupational exposure to toluene diisocyante (TDI) can occur during production, handling and use,94 and emissions from urethane production facilities can lead to exposure in the general population 95. TDI‐induced asthma shares similarities with common environmental asthma (natural history, clinical symptoms, and pathology) but also differences (minimal Th2 response, minimal association of atopy, allergen‐specific IgE and serum levels of total IgE) 96.…”
Section: Adaptive Immune Responsementioning
confidence: 99%